Integration processes in Asia-Pacific region (International relations and international law Journal, 2016)
The article discusses the integration processes in the Asia-Pacific region. In the geopolitical plane, Asia-Pacific region is the one of the spaces of interests’ intersection of major power centers. This region acts as a springboard for the states on both sides of the ocean. Since the end of the last century, the grouping of region countries and the integration process gained a new turn. Asia-Pacific trade is important because it is huge, innovative and dynamically develops. Asia-Pacific region has the strategic importance for the world. The economies of countries called Asian «tigers» and «dragons», is developing rapidly and is at the leading position in the world on economic indicators.
Keywords: integration processes; Asia-Pacific region; Asian path of integration; Trans-Pacific path of integration; ASEAN